On Empresses of the Latin Empire (1204–1261). Yolanda of Flanders - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 2022)
The article is the third part of the series ‘On Empresses of the Latin Empire (1204–1261)’. The article is the second part of the series On Empresses of the Latin Empire (1204–1261). This one is dedicated to Yolanda of Flanders, the second wife of Peter II of Courteney. Yolanda became empress in 1217, lost her husband the same year, and probably gave birth to Baldwin in 1218. It did not play any significant role in the history of the Latin Empire.